1986
DOI: 10.1002/prac.19863280404
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modelling of the Oxidation of Medium Paraffins further evidence for the importance of bifunctional intermediates

Abstract: By computer simulation of the dependencies of the mole numbers of the ketones and alcohols derived from the starting paraffin, of the acids and esters, and in some cases also of the lower alkan‐2‐ones on the paraffin conversion relative rate constants were determined on the basis of a plausible kinetic model of the paraffin oxidation. The data obtained show that about 67% of the oxidation proceeds via bifunctional primary products. With the aid of the relative rate constants determined a good simulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Stark et al, also suggests that the formation of shorter-chain-length species may occur early in the process with a breaking to the C–C bond upon formation of an aldehyde from an alkoxyl radical (hydroperoxide decomposition product). The formation of γ-lactones from n -alkanes has been suggested by Engelmann et al and is one of many reactions proposed for their decomposition. This is also supported by Stark et al, in which oxidation of the branched alkane pristane resulted in two lactones being identified, specifically 5,5-dimethyldihydrofuran-2-one and 5-methyl-5-(4-methyl-pentyl)dihydrofuran-2-one.…”
Section: Resultsmentioning
confidence: 95%
“…Stark et al, also suggests that the formation of shorter-chain-length species may occur early in the process with a breaking to the C–C bond upon formation of an aldehyde from an alkoxyl radical (hydroperoxide decomposition product). The formation of γ-lactones from n -alkanes has been suggested by Engelmann et al and is one of many reactions proposed for their decomposition. This is also supported by Stark et al, in which oxidation of the branched alkane pristane resulted in two lactones being identified, specifically 5,5-dimethyldihydrofuran-2-one and 5-methyl-5-(4-methyl-pentyl)dihydrofuran-2-one.…”
Section: Resultsmentioning
confidence: 95%
“…Apparently, the high activation energy required for R02* intramolecular isomerization involving secondary C-H bonds was not met at their test temperatures. Aside from ethers, other products such as alkanoic acids, methyl ketones, and 1-oxyalkanes have been identified during roalkane autoxidations by Jenson et al 27 Additionally, Engelmann et al 28 identified that acids -lactones, 2-alkan-2-ones, and esters are formed via bifunctional primary products.…”
Section: Discussionmentioning
confidence: 99%